The Self-esteem Stability Scale (SESS) for Cross-Sectional Direct Assessment of Self-esteem Stability - Altmann, Tobias; Roth, Marcus (Frontiers in Psychology, 2018)
Self-esteem stability describes fluctuations in the level of self-esteem experienced by individuals over a brief period of time. In recent decades, self-esteem stability has repeatedly been shown to be an important variable affecting psychological functioning. However, measures of self-esteem stability are few and lacking in validity. In this paper, we present the Self-Esteem Stability Scale (SESS), a unidimensional and very brief scale to directly assess self-esteem stability. In four studies (total N = 826), we describe the development of the SESS and present evidence for its validity with respect to individual outcomes (life satisfaction, neuroticism, and vulnerable narcissism) and dyadic outcomes (relationship satisfaction in self- and partner ratings) through direct comparisons with existing measures. The new SESS proved to be a stronger predictor than the existing scales and had incremental validity over and above self-esteem level. The results also showed that all cross-sectional measures of self-esteem stability were only moderately associated with variability in self-esteem levels assessed longitudinally with multiple administrations of the Rosenberg Self-Esteem Scale. We discuss this validity issue, arguing that direct and indirect assessment approaches measure relevant, yet different aspects of self-esteem stability.